2012
DOI: 10.1128/jcm.06609-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Several Biochemical and Molecular Techniques for Identification of Streptococcus pneumoniae and Streptococcus pseudopneumoniae and Their Detection in Respiratory Samples

Abstract: The identification and detection of mitis group streptococci, which contain Streptococcus pneumoniae, have been hampered by the lack of sensitive and specific assays. In this study, we evaluated several biochemical and molecular assays for the identification of S. pneumoniae and Streptococcus pseudopneumoniae and their distinction from other mitis group streptococci using a collection of 54 isolates obtained by the routine culturing of 53 respiratory specimens from patients with community-acquired pneumonia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…However, it involves more inputs and selection of other genes out of a few thousand genes within the genome is not an easy task. In spite of the fact that around 23 genes have been used frequently in many studies carried out for identifying Streptococcus, no consensus gene has been identified [3,4,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It has also not been realized that except recA, the rest of the 22 genes are not present in all the species of Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it involves more inputs and selection of other genes out of a few thousand genes within the genome is not an easy task. In spite of the fact that around 23 genes have been used frequently in many studies carried out for identifying Streptococcus, no consensus gene has been identified [3,4,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It has also not been realized that except recA, the rest of the 22 genes are not present in all the species of Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…A few genes which are frequently used for the identification of Streptococcus include genes: cpsA, gdh, groESL, lytA, ply, psaA, pspA, recA, recN, rpoA, rpoB, sodA, tuf, wzg, 16S-23S ribosomal DNA spacer region, and the DNA fragment Spn9802 [3,4,11,[22][23][24][25][26][27][28][29][30][31]. Optochin susceptibility testing (CO 2 atmosphere) in combination with amplification of Spn9802 fragment and the autolysin genes: lytA, rpoB, and tuf, have proved effective in identifying S. pneumoniae [32]. It must be realized that the most idyllic rrs gene is offering no escape as human beings are struggling to reach a consensus, while pathogenic bacteria are threatening our long-term survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betahemolytic colonies were tested with bacitracin susceptibility and a latex agglutination test (Oxioid, USA) for Lancefield classification. Alpha-hemolytic colonies were pursued with the optochin disc test (Oxioid, USA) and bile solubility test [12]. All strains were kept as 15 % glycerol stocks in a -80°C freezer.…”
Section: Bacteriological Methodsmentioning
confidence: 99%
“…Clearing of the test suspension within 3 h was considered to be positive test (Wessels et al, 2012). All S. pseudopneumoniae isolates included in this study were phonotypically suspected as being capsule free, sensitive to optochin in ambient air but intermediate or resistant by incubation in 5% CO2 and bile insoluble.…”
Section: Bile Solubility Testmentioning
confidence: 99%